The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1021/jf500857e
|View full text |Cite
|
Sign up to set email alerts
|

Milling, Water Uptake, and Modification Properties of Different Barley (Hordeum vulgareL.) Lots in Relation to Grain Composition and Structure

Abstract: Milling properties, water uptake, and modification in malting were studied in 14 barley (Hordeum vulgare L.) lots from two consecutive crop years. In all barley lots studied, grains with lower β-glucan and protein content and higher starch content produced finer flours upon milling. Grains with lower β-glucan content also hydrated more rapidly during steeping. A detailed study of two cultivars from two crop years indicated that similar environmental conditions could induce a higher β-glucan content and concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
4
6
1
Order By: Relevance
“…Starch is the major carbohydrate in all cereals and contributes significantly to energy intake, while the sugars are found in barley grain at very low concentrations (Gray, Abdel‐Alal, Seetharaman, & Kakuda, 2010). The starch contents obtained in the present study are in the range of 52.2% to 59.2% dw, which was below that of most of the published values (Abdel‐Aal & Choo, 2014; Åman et al., 1985; Griffey et al., 2010; Holopainen et al., 2014). Some investigators reported starch values similar to the ones reported here, such as Ragaee et al.…”
Section: Resultscontrasting
confidence: 90%
See 2 more Smart Citations
“…Starch is the major carbohydrate in all cereals and contributes significantly to energy intake, while the sugars are found in barley grain at very low concentrations (Gray, Abdel‐Alal, Seetharaman, & Kakuda, 2010). The starch contents obtained in the present study are in the range of 52.2% to 59.2% dw, which was below that of most of the published values (Abdel‐Aal & Choo, 2014; Åman et al., 1985; Griffey et al., 2010; Holopainen et al., 2014). Some investigators reported starch values similar to the ones reported here, such as Ragaee et al.…”
Section: Resultscontrasting
confidence: 90%
“…Some investigators (Åman et al., 1985) found that the starch content of the six‐row varieties was higher than that in two‐row varieties, which coincides with the results here obtained; however, Holopainen et al. (2014) found the opposite. Therefore, the number of rows and spike density, genetically determined, influenced the proximate chemical composition of the barley landraces.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Many authors (e.g. Holopainen et al, 2014) have found a significant negative correlation between the nitrogenous substance content and the starch content. Generally, the level of 10.8-11.2% of nitrogenous substance content is required.…”
Section: Results and Disscussionmentioning
confidence: 99%
“…They include zein in corn (Anderson & Lamsal, 2011), gliadin in wheat (Payne, Holt, Lawrence, & Law, 1982), hordein in barley (Tatham & Shewry, 2012), and kafirin in sorghum (Hamaker, Mertz, & Axtell, 1994). Prolamins can be classified into subgroups depending on their molecular weight (M w ) and amino acid composition (Holopainen et al., 2014; Qi, Wei, Yue, Yan, & Zheng, 2006; Wu, Myers, & Johnson, 1997), factors that determine their physical and chemical properties (Trevino, Scholtz, & Pace, 2007). Moreover, their unique biocompatibility, biodegradability, and nutritional functionalities offer promising potential in food applications (Soltani & Madadlou, 2016).…”
Section: Introductionmentioning
confidence: 99%